2009
DOI: 10.1016/j.ejpain.2008.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Pentoxifylline attenuates nociceptive sensitization and cytokine expression in a tibia fracture rat model of complex regional pain syndrome

Abstract: Background-Tibia fracture in rats evokes chronic hindpaw warmth, edema, allodynia, and regional osteopenia, a syndrome resembling complex regional pain syndrome (CRPS). Previous studies suggest that the pathogenesis of some of these changes involves an exaggerated regional inflammatory response to injury and we postulated that inflammatory cytokines contribute to the development of CRPS-like changes after fracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(77 citation statements)
references
References 66 publications
(91 reference statements)
1
75
1
Order By: Relevance
“…This effect is possibly due to the reduction of the formation of endoperoxides as a consequence of the elevated cAMP levels that inhibit the cyclooxygenase within the arachidonic pathway (29). Furthermore, it is been shown that pentoxifylline both enhances morphine's analgesic effects by targeting microglial activation during morphine therapy/ treatment in mice (30) and also decreases pro-infl ammatory cytokines contributing to nociceptive in rats (31).…”
Section: Discussionmentioning
confidence: 99%
“…This effect is possibly due to the reduction of the formation of endoperoxides as a consequence of the elevated cAMP levels that inhibit the cyclooxygenase within the arachidonic pathway (29). Furthermore, it is been shown that pentoxifylline both enhances morphine's analgesic effects by targeting microglial activation during morphine therapy/ treatment in mice (30) and also decreases pro-infl ammatory cytokines contributing to nociceptive in rats (31).…”
Section: Discussionmentioning
confidence: 99%
“…As stated earlier, substance P activation also leads to the over-expression of the inflammatory cytokines (Wei et al, 2009), for example, nerve growth factor is one of the cytokines that leads to osteopenia. The use of a nerve growth factor antibody not only reduced nociception but to a modest degree, maintained further bone loss in the distal trabecular bone (Sabsovich et al, 2008).…”
Section: Neuropeptide Modulatorsmentioning
confidence: 99%
“…The use of a nerve growth factor antibody not only reduced nociception but to a modest degree, maintained further bone loss in the distal trabecular bone (Sabsovich et al, 2008). Pentoxifylline, a cytokine inhibitor, was used to evalute its effect in trabecular bone loss (Wei et al, 2009). Pentoxifylline had significant effects in the fracture induced up-regulation of inflammatory cytokines and reversed nociceptive sensitization and vascular abnormalities.…”
Section: Neuropeptide Modulatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pentoxifylline (PTX) is a nonselective phosphodiesterase inhibitor that is further known for its broad-spectrum cytokine inhibitory properties [Wei et al 2009;Lin et al 2010]. It has been used clinically in a wide variety of conditions.…”
Section: Growth Factorsmentioning
confidence: 99%